Avidly Reads Opera. - Kinney, Alison (New York University Press, 2021)
"Opera is community, comfort, art, voice, breath, life. It's hope."All art exists to make life more bearable. For Alison Kinney, it was the wild, fantastical world of opera that transformed her listening and her life. Whether we're listening for the first time or revisiting the arias that first stole our hearts, Avidly Reads Opera welcomes readers and listeners to a community full of friendship, passion, critique--and, always, beautiful music. In times of delirious, madcap fun and political turmoil, opera fans have expressed their passion by dispatching records into the cosmos, building fairy-tale castles, and singing together through the arduous work of social activism. Avidly Reads Opera is a love letter to the music and those who love it, complete with playlists, a crowdsourced tip sheet from ultra-fans to newbies, and stories of the turbulent, genre-busting, and often hilarious history of opera and its audiences.Across five acts--and the requisite intermission--Alison Kinney takes us everywhere opera's rich melodies are heard, from the cozy bedrooms of listeners at home, to exclusive music festivals, to protests, and even prisons. Part of the Avidly Reads series, this slim book gives us a new way of looking at culture. With the singular blend of personal reflection and cultural criticism featured in the series, Avidly Reads Opera is an homage to the marvelous, sensational world of opera for the casual viewer.